Current Strategies to Minimize Ischemia-Reperfusion Injury in Liver Transplantation: A Systematic Review - Gazia, Carlo; Lenci, Ilaria; Manzia, Tommaso M; Martina, Milana; Tisone, Giuseppe; Angelico, Roberta; Abenavoli, Ludovico; Grassi, Giuseppe; Signorello, Alessandro; Baiocchi, Leonardo (Reviews on Recent Clinical Trials, 2021)
Background: Hepatic Ischemia Reperfusion Injury (IRI) is a serious threat that characterizes the liver but also other transplantable organs. The worst effect of long-term IRI on an impaired graft could lead to irreversible damage and organ failure. Several events characterize the cascade that ultimately leads to organ failure. Among all, multiple strategies have been attempted to identify early phenomena of IRI with divergent results, and biomarkers might represent a novel approach to early detect ischemic damage. Methods: A literature review of the current state-of-the-art on IRI was conducted in the present manuscript. Information was collected from worldwide clinical trials conducted in highly specialized institutions. Experiments conducted on IRI animal models and clinical studies were screened. The final outcomes were analyzed and reported in the present review. Results: Matrix Metalloproteinases (MMPs) represent an interesting example of the early detector of neutrophil invasion after acute and chronic hepatic IRI. Neutrophil Gelatinase-associated Lipocalin (NGAL) is another biomarker which seems more predictable of the IRI gravity phase. Mitochondrial flavin mononucleotide (FMN) was recently discovered and might become a reliable biomarker of hepatic IRI during Hypothermic Oxygenation Machine Perfusion (HOPE). Conclusion: The available strategies to avoid IRI, despite constantly improving, are still lacking a gold standard method. Further studies are still needed to explore new options in the IRI diagnosis and treatment, and to this purpose, regenerative medicine and tissue engineering surely can play a pivotal role in the transplantation field.
Keywords: biomarkers